Influence of Janus particle shape on their interfacial behavior at liquid-liquid interfaces - Ruhland, Thomas M (Langmuir : the ACS journal of surfaces and colloids, 2013)
We investigate the self-assembly behavior of Janus particles with different geometries at a liquid-liquid interface. The Janus particles we focus on are characterized by a phase separation along their major axis into two hemicylinders of different wettability. We present a combination of experimental and simulation data together with detailed studies elucidating the mechanisms governing the adsorption process of Janus spheres, Janus cylinders, and Janus discs. Using the pendant drop technique, we monitor the assembly kinetics following changes in the interfacial tension of nanoparticle adsorption. According to the evolution of the interfacial tension and simulation data, we will specify the characteristics of early to late stages of the Janus particle adsorption and discuss the effect of Janus particle shape and geometry. The adsorption is characterized by three adsorption stages which are based on the different assembly kinetics and different adsorption mechanisms depending on the particle shape